Factors contributing to increased use of Herbal Medicine among Pregnant Women aged 18-45 years attending Buwambo Health Centre IV, Wakiso District. A Cross-sectional Study. - Kitara , Mercy; Kalungi, Vincent Charles (Student’s Journal of Health Research Africa, 2022)
Background: The purpose of the study was to determine the factors contributing to the increased use of herbal medicine among pregnant women aged 18-45 years attending Buwambo Health Centre IV, Wakiso District. The specific objectives were to determine the: Maternal, Socioeconomic, and health facility-related factors contributing to the increased use of herbal medicine among pregnant women aged 18-45 years. Methodology: The study design was descriptive and cross-sectional and the researcher employed the simple random sampling technique. The study instrument was a questionnaire and a sample of 50 respondents was used. Medicine because they were readily available. Results: Regarding the health facility-related factors contributing to increased use of herbal medicine, the majority (74%) of the respondents reputed that the health workers took a lot of time to work on them, and most (40%) had their homes more than 10km away from the health facility and more than half (52%) waited over 2hrs to be seen by the doctor. Conclusion: Maternal factors contributing to increased use of herbal medicine included having information about herbal medicine from family members (70%), being in the first trimester (76%), and the pregnancy-related complications such as nausea and vomiting (40%), socio-economic factors were; encouragement by their culture and religion (60%), availability of herbal medicine (56%), health facility-related factors were; long waiting hours (74%), and long-distance from the health facility (40%). Recommendation: The researcher recommended the Ministry of Health put up more health facilities to reduce the distance moved by the pregnant women while looking for the antenatal care services and that Buwambo Health Centre IV should intensify health education the pregnant women on the importance of antenatal care visits and the implications of the use of herbal medicine during pregnancy.